Mental health outcomes in pregnant women with relapsing-remitting multiple sclerosis: a longitudinal cohort study - Pfeffer, Lena Kristina; Ramien, Caren; Harrison, Anja; Patas, Kostas; Grentzenberg, Kristina; Reinhardt, Stefanie; Mönch, Andrea; Kaufmann, Max; Gold, Stefan M.; Heesen, Christoph (Frontiers in Neurology, 2025)
IntroductionSince multiple sclerosis (MS) primarily affects women of childbearing age, the disease intersects with a critical period for family planning and pregnancy. This is important, since pregnancy itself can influence psychological well-being, contributing to symptoms such as depression, stress and fatigue. However, while mental health during late pregnancy and the postpartum period has been studied in women with multiple sclerosis (wwMS), data on longitudinally tracking mental health in wwMS across all trimesters of pregnancy are still limited.MethodsIn this prospective cohort study, we assessed the frequency and severity of depression, stress and fatigue in 95 women with relapsing-remitting MS (RRMS) throughout the course of pregnancy and postpartum using a set of psychological questionnaires. Furthermore, we evaluated the frequency and disease-specific risk factors of postpartum depression.ResultsOver the course of pregnancy, there was no relevant increase in depressive symptoms, fatigue or stress. Moderate to high risk of postpartum depression was evident in 19.8% of wwMS and positively correlated with an increase in Expanded Disability Status Scale (EDSS) (r = 0.237, p adj = 0.049) during pregnancy but not with baseline EDSS.DiscussionOur data suggest that pregnancy does not generally increase the risk of stress, depression, or fatigue in wwMS, which is reassuring for both wwMS and their treating physicians. However, given the higher susceptibility to mental health alterations in MS, regular screening for mental health disturbances remains crucial. In particular, wwMS with disability progression during pregnancy should be closely monitored for postpartum depression.